Pengaruh Penyuluhan Menggunakan Media Animasi Terhadap Pengetahuan Personal Hygiene Pada Siswa Di Mi Negeri Baki Sukoharjo - Nur Rohmah, Fitri, Elida Soviana, S.Gz., M.Gizi, Dyah Widowati, SKM (2015)
Introduction: Hygiene is a disease prevention that focuses on the business environment and their personal health. Personal hygiene that not good can cause diseases such as infectious diseases. The infection is carried by germs through human senses. A person with infectious diseases can reduce appetite so malnourished. Objective: There purpose of this research was to know the influence of illumination of using animation media to personal hygiene knowledge to the students in MI Negeri Baki Sukoharjo. Methods: This research used quasy experimental study with one group pre and posttest design. While the sample was fifth grade students in MI Negeri Baki Sukoharjo. The researcher took the data using simple random sampling. Personal hygiene knowledge was obtained with filling the questionnaire. The test of effect that used in this study was Wilcoxon Signed Rank Test. Results: This study showed that most of the students' level of knowledge about personal hygiene before the extension animation media got a good category consist 29 subjects (67,5%), sufficient category consist of 13 subjects (30,2%), less category consist of 1 subjects (2,3%) and after given counseling, got a good category 1 subjects (95,3%), sufficient category consist of 2 subjects (4,7%), with the result of value of p=0.000. Conclusions: There is influence of illumination using animation media for personal hygiene knowledge to the students in MI Negeri Baki Sukoharjo.